The Lyman Continuum Escape Fraction of Star-forming Galaxies at 2.4 ≲ z ≲ 3.0 from UVCANDELS - Xin Wang; Harry I. Teplitz; Brent M. Smith; Rogier A. Windhorst; Marc Rafelski; Vihang Mehta; Anahita Alavi; Zhiyuan Ji; Gabriel Brammer; James Colbert; Norman Grogin; Nimish P. Hathi; et al. (The Astrophysical Journal)
The UltraViolet Imaging of the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey Fields (UVCANDELS) survey is a Hubble Space Telescope (HST) Cycle-26 Treasury Program, allocated in total 164 orbits of primary Wide-Field Camera 3 Ultraviolet and VISible light F275W imaging with coordinated parallel Advanced Camera for Surveys F435W imaging, on four of the five premier extragalactic survey fields: GOODS-N, GOODS-S, EGS, and COSMOS. We introduce this survey by presenting a comprehensive analysis of the absolute escape fraction ( ${f}_{{\rm{esc}}}^{{\rm{abs}}}$ ) of Lyman continuum radiation through stacking the UV images of a population of star-forming galaxies with secure redshifts at 2.4 ≤ z ≤ 3.0. Our stacking benefits from the catalogs of high-quality spectroscopic redshifts compiled from archival ground-based data and HST slitless spectroscopy, carefully vetted by dedicated visual inspection efforts. We develop a robust stacking method to apply to 10 samples of in total 56 galaxies, and perform detailed Monte Carlo simulations of the intergalactic medium (IGM) attenuation, to take into account the sample variance of the mean IGM transmission when measuring ${f}_{{\rm{esc}}}^{{\rm{abs}}}$ . The full stack at z ≈ 2.44 from 28 galaxies places a stringent 1 σ upper limit of ${f}_{{\rm{esc}}}^{{\rm{abs}}}\lesssim 5 % $ , whereas the full stack at z ≈ 2.72 of an equal number of galaxies gives an upper limit of ${f}_{{\rm{esc}}}^{{\rm{abs}}}\lesssim 26 % $ at 1 σ confidence level. These new F275W and F435W imaging mosaics from UVCANDELS have been made publicly available on the Barbara A. Mikulski Archive for Space Telescopes.